2019
DOI: 10.3389/fnut.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain During Treatment of Bipolar Disorder (BD)—Facts and Therapeutic Options

Abstract: Bipolar disorder (BPD) is a mood disorder, which is characterized by alternating affective states, namely (hypo)mania, depression, and euthymia. Evidence is growing that BPD has indeed a biologic substrate characterized by chronic inflammation, oxidative stress, and disturbed energy metabolism. Apart from this, there is obviously a hereditary component of this disease with multi-genetic factors. Most probably a susceptibility threshold favors the outbreak of clinical disease after a cascade of stress events th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Whether weight loss alone could lead to a reduction in symptoms of depression, bipolar disorder ( 64 ), and/or psychosis remains a largely unanswered question. In people with type 2 diabetes treated with a KD, improvement in depression symptoms was not correlated with weight loss ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether weight loss alone could lead to a reduction in symptoms of depression, bipolar disorder ( 64 ), and/or psychosis remains a largely unanswered question. In people with type 2 diabetes treated with a KD, improvement in depression symptoms was not correlated with weight loss ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amenorrhea might be an adverse effect of stress, depression, and affective disorders (Facchinetti et al, 1993). Furthermore, as described previously, BD is also associated with overweight and obesity due to polygenetic disposition, biological processes such as inflammation, and unhealthy lifestyle (Mangge et al, 2019). It is therefore not surprising that there is also a higher rate of symptoms related to "sexuality and body weight" in BD.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, anti-sense apo-B oligonucleotides and MTTP (Microsomal triglyceride transfer protein) inhibitors employed in managing lipid disorders can cause the ectopic deposition of fat, especially in the liver, and changes the fat distribution in the body [ 12 ]. It is well established that antidepressants, atypical antipsychotics, and mood-stabilizing agents induce weight gain by increasing appetite [ 13 ]. A UK study in 136,762 men and 157,957 women demonstrated that the use of antidepressants was associated with weight gain at the population level and suggested that the risk for weight gain must be considered during the antidepressant treatment [ 14 ].…”
Section: Drugs-induced Obesitymentioning
confidence: 99%